Conservation Status of Bird Species on Promasan Hiking Trail, Mount Ungaran, Central Java - Purnamaningrum, Arifah; Bihi, Moh Kafa; Harits, Anif Risqianti (Jurnal Biologi Tropis, 2021)
Mount Ungaran is one of the dormant volcanoes in Central Java. The condition of the unspoiled forest in the Mount Ungaran area is a good habitat for fauna, including birds. There are several hiking trails traversed by mountain climbers, one of them is the Promasan hiking trail. This study aims to determine the diversity of bird species and identify their conservation status on the Promasan hiking trail. Data were colected by Indices Ponctuels d’Abondance (IPA), Line Transect, and Point Count methods. Bird species diversity was determined by the Shanon index. Determination of bird conservation status based on the IUCN Red List, CITES Appendix, Government Regulation (PP No. 7 of 1999) and Ministry of Environment and Forestry Regulation (PERMENLHK RI No. 106, 2018). The results showed that there were 24 bird species belonging to 19 families. The diversity of bird species was classified as moderate (Shanon index = 2.59). There were two species including CITES Appendix II. Based on the IUCN Red List, there was one species in the Endangered (EN) category, 23 species in the Least Concern (LC) category. There was one species that is protected according to Government Regulation (PP No. 7 of 1999). The 3 species include as protected under the Ministry of Environment and Forestry Regulation (PERMENLHK RI No. P.106, 2018). Monitoring the presence of birds in this area must be carried out regularly.